Yudja Utaha: a culinária juruna no Parque Indígena Xingu - uma contribuição ao dicionário bilíngue juruna-português - Mondini, Juliana Nazatto [UNESP] (2014)
This dissertation presents the study of organization of a vocabulary of the lexicon focused in the semantic field of the Juruna cookery. The Juruna language is a Brazilian indigenous language, of the Juruna Family, related to the Tupi Stock, spoken by 458 people (according to recent census) in the Xingu Indigenous Park (MT). The lexicographical organization of this vocabulary aims to collaborate in the making of the bilingual Juruna-Portuguese illustrated encyclopaedic dictionary (larger research project, coordinated by the advisor of this research). The raw data were collected by the methods of participant observation and semi-structured interviews, during the years 2011 to 2013 in Maitxiri-Tubatuba village, which has larger demographic density. This dissertation contains: a short history about the first contacts with the Juruna people; the scientific studies that guide us for the organization of the acquired knowledge, with theoretical basis on the Functionalism and theoretical approaches for the Studies of the Lexicon; the development of the field and office works; the analyses of group the lexical units; the lexicographical decisions for the treatment of the headwords; and the 72 headwords